Pioglitazone Attenuates Reoxygenation Injury in Renal Tubular NRK-52E Cells Exposed to High Glucose via Inhibiting Oxidative Stress and Endoplasmic Reticulum Stress - Zou, Cong; Zhou, Zhiyu; Tu, Yunming; Wang, Weichao; Chen, Tongchang; Hu, Honglin (Frontiers in Pharmacology, 2020)
Renal ischemia-reperfusion injury (IRI) is a major cause of acute kidney injury. In the present study, we investigated the effects of pioglitazone on hypoxia/reoxygenation (H/R) injury in rat renal tubular epithelial cells (RTECs) under normal- or high-glucose culture conditions via evaluating oxidative stress and endoplasmic reticulum stress (ERS). The RTECs (NRK-52E cells) were divided into six groups as follows: normal-glucose (NG) group, high-glucose (HG) group, NG+H/R group, HG+H/R group, NG+Pio+H/R group, and HG+Pio+H/R group, among which cells in H/R groups were subjected to 4 h of hypoxia followed by 12 h of reoxygenation. After that, the cells were evaluated using the Cell Counting Kit-8 (CCK-8) assay for the determination of their viability and flow cytometry assay for the detection of apoptosis. The levels of superoxide dismutase (SOD), glutathione reductase (GSH), catalase (CAT), and malondialdehyde (MDA) were determined via colorimetric chemical assays. In addition, the expression of ERS-associated proteins, i.e., ATF4, ATF6, GRP78, and CHOP, was determined via western blotting. A high-glucose environment could reduce the viability and increase the apoptotic rate of NRK-52E cells with increased MDA levels and decreased SOD, CAT, and GSH levels, and upregulate the expression of ERS-associated proteins, i.e., ATF4, ATF6 and GRP78. H/R injury could further aggravate changes in the above indicators, but pioglitazone could significantly reverse such changes and alleviate cell injury. Thus, Pioglitazone exhibits a cytoprotective effect on RTECs against H/R injury under normal- or high-glucose culture conditions by inhibiting oxidative stress and ERS.